Geronimo's Valentine - Stilton, Gernimo (New York Scholastic Inc., 2024)
Who is Geronimo Stilton? That's me! I run a newspaper but my true passion is writing tales of adventure. Here is New Mouse City, the capital of Mouse Island My books are all bestsellers!! My stories are full of fun tastier than Swiss cheese and tangier than extra-sharp cheddar. They are whisker-licking good stories and that's a promise! Geronimo's Valentine: I'll admit it, I'm a bit of a cheesy mouse. What can I say? I'm a romantic! That's why I love Valentine's Day. This year I had a date with a very special rodent Petunia Pretty Paws! But then my private investigator friend, Hercule Poirat, called. He needed my help solving a mystery. Now I had to help Hercule and impress Petunia at the same time. Holey cheese, what was a gentle-mouse to do?
Keywords: Fiction